Economic analysis of solar energy systems using spreadsheets - Kalogirou, Soteris A. (My University, 1996)
In this paper the method employed for a detailed economic analysis of a solar energy system is presented. A spreadsheet computer program is used as a tool for the economic analysis because the general format of such a program is a table with cells which can contain values or formulae and the fact that they incorporate many build-in functions. System optimisation is also presented through an example for a hot water system. Both of them show that the method presented here is both accurate and fast. Although the method presented here deals with solar systems, it is applicable to all energy producing systems and consequently to all renewable energy systems.
Keywords: Economic analysis; Life cycle analysis; Life cycle cost; Llife cycle savings